2015
DOI: 10.1016/j.crad.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Breast DWI at 3 T: influence of the fat-suppression technique on image quality and diagnostic performance

Abstract: The fat-saturation technique used in the present study may influence image quality and ADC quantification. Nevertheless, STIR and SPAIR techniques showed similar diagnostic performances, and therefore, both are suitable for use in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…Another group [32] reports that the CV R was 1.5 % on phantoms, and less than 4 % for cerebral parenchyma. Impact of acquisition parameters has also been investigated [3335]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group [32] reports that the CV R was 1.5 % on phantoms, and less than 4 % for cerebral parenchyma. Impact of acquisition parameters has also been investigated [3335]. …”
Section: Discussionmentioning
confidence: 99%
“…Another group [ 32 ] reports that the CV R was 1.5 % on phantoms, and less than 4 % for cerebral parenchyma. Impact of acquisition parameters has also been investigated [ 33 35 ]. Impacts of post-processing software were documented by Zeilinger et al [ 36 ], reporting up to 8 % variation when ADC was processed by four different types of software.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison between two commonly used techniques for breast DWI, SPAIR, and STIR, on fat-suppression uniformity, SNR, CNR, image quality, lesion visibility, and ADC values, have been reported before. 25,26 It was found that STIR could achieve a better uniformity compared with SPAIR, but SPAIR had slightly improved lesion visibility. Their SNR and CNR, and also the overall diagnostic performance, were comparable; thus, it was concluded that both techniques were suitable for use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from low SNR, a commonly encountered problem is insufficient fat suppression, which leads to ghosting and potentially to underestimation of ADC values. Spectral attenuated inversion recovery (SPAIR), which employs both T1 contrast and spectral selectivity, is recommended given a moderate preference in literature in comparison with short tau inversion recovery (STIR) [59,60] and based on the consensus among the panel. However, if unsuccessful, STIR may be an acceptable alternative as this technique is independent from B 0 field inhomogeneity [61].…”
Section: What Sequence Type and Parameters Are Recommended For Breastmentioning
confidence: 99%